ANALISIS MINAT BELAJAR SISWA TERHADAP MATA PELAJARAN MATEMATIKA DI KELAS VII SMP NEGERI 5 RAMBAH SAMO - septianingsih, rika; Arcat, Arcat (Jurnal Edu Research, 2024)
The research aims to analyze and describe the learning interestts of class VII students at SMP Negeri 5 Rambah Samo. This type of research is descriptive qualitative research. The subjects of this research are class VII students consisting of two classes totaling 40 students who were determined using the saturated sampling method. Data collection tecniques used questionnaires and interviews. Student learning interest in terms of the indicator of feeling happy was in the quite interested category with a percentage of 70.63%. Students learning interest in terms of the student’s attention indicator was in the quite interested category with a percentage of 70.34%. Students are in the quite interested category with a percentage of 72.38%. Students learning interest in terms of indicators of student involvement is in the very high category with a percentage of 75.05%. So the results of overall student interest in learning are in the quite interested category with a percentage of 72.08%.